Poetry and ’mediation’ - Tortosa, Virgilio (Tropelías: Review of Literary Theory and Comparative Literature, 2023)
Little margin is left by the market for the creation of a work fully autonomous from the impulses of a media age. The mass media dynamize the totality of reality, including the lyrical creation of our time, managing the rhythm and its modes of dynamization. Poets, more often than not, submit to the media demands that modulate the work and the way of reading, when they do not start from their connatural alliance. Screens of all kinds are inevitable mediators that build poetic reality already past and present, in an unprecedented exercise of screening and reinstatement. It proposes a reflection of the creative processes ―already contemporary, already historical―, rediscursivized in our present from the remediation generated by the disseminating devices of our time.